Analisis Efisiensi Penerapan Internal Control Atas Retribusi Parkir Pada Dinas Perhubungan Kabupaten Kediri - Ardani, Anichah Isma; Latifaturrohmah, Alifiya; Hermanita, Diana Fitria (Universitas Muhammadiyah Gresik, 2024)
This study examines the efficiency of implementing internal controls on parking fee collections by the Transportation Department of Kediri Regency. It primarily focuses on evaluating the effectiveness of control measures over both regular and subscription parking fees, which contribute to the region’s locally generated revenue (PAD). The methodology involved interviews and document analysis to assess the accounting systems and collection procedures in place.The subscription parking levy procedure starts with the head of the department ordering the data collection, after that the head of the regional police department collects the subscription parking levy data, then the parking officer prepares the subscription parking levy data guidelines and then finally repairs, prints and saves the file.The research results show that there are weaknesses in internal control, especially in the aspect of multiple functions and lack of documentation, which increases the potential for fraud to occur. Type of Paper: Review Keywords: Control, Collection, Efficiency.